Rekayasa Penyediaan Produk Non Pangan Berbentuk Detergen Cair Berbahan Lidah Buaya dan Daun Kesum - Gunawan, Desdy H (Politeknik Negeri Pontianak, 2024)
This research concerns the provision of plant-based liquid detergents that are friendly to the environment and users. The materials used are aloe vera and kesum leaves. The products produced are targeted to meet the needs of detergents with specifications that are cheap, easy to use and environmentally friendly so that they are very safe for the surrounding environment against waste after use. The aim of the research was to formulate the amount of aloe vera and kesum leaf extracts in the manufacture of liquid detergent followed by chemical and physical characterization of the resulting liquid detergent. The stage of the research is to formulate the use of aloe vera and kesum leaves with 5 combinations, namely 50:50. 40:60. 30:70. 20:80 and 10:90 (comparison of aloe vera: kesum leaf) followed by chemical and physical tests which include: pH, foam stability, irritation, color and odor. The resulting liquid detergent samples have a pH range of 2.34 to 2.93 which is considered safe for the skin and does not cause irritation to the skin. The resulting foam stabilizes in the range of 87 to 99, while the resulting color is relatively green due to the chlorophyll content in kesum leaves and affects the aroma produced due to the content of aromatic compounds.